DEPRESSIVE SYMPTOMS, SOCIAL SUPPORT, AND SEVERITY OF HEART DISEASE IN AN INTERNATIONAL COHORT STUDY. (11th November 2018) - Smalls, B; Miller, J; Moser, D
Abstract: Depressive symptoms and social support are significant risk factors for poor prognosis in cardiac patients, and literature suggests that social support can independently predict adverse outcomes. As the population ages, heart disease continues to be a leading cause of death. Using a prospectively collected international dataset that includes participants from the US, Asia, Europe, and Australia, we sought to analyze and understand the relationship between depressive symptoms, social support and severity of heart disease in older adults. Participants (N=4, 975) were, on average, 74 years old (SD±6.4), mostly male (65%), had attended college (40%), were of northern European ethnicity (57%), married/cohabitated (58.6%), and residents of the US (55%). We conducted analyses to determine if depressive symptoms mediated the relationship between social support and heart disease severity. We found statistically significant relationships between social support and depressive symptoms (□=-14.8, p<0.001) and depressive symptoms and disease severity (□=0.13, p<0.001). There was not a statistically significant relationship between social support and disease severity (□=0.06, p<0.001). However, the relationship was statistically significant in the unadjusted model with social support predicting depressive symptoms (□=-10.9, p<0.001) and disease severity (□=1.8, p=0.023). In the model adjusted for covariates, social support independently predicted depressive symptoms (□=-2.1, p=0.163) and disease severity (□=4.2, p=0.001). This suggests that while depressive symptoms have a relationship with social support and disease severity, it does not operate as a mediator in this sample. These results indicate a need to address inadequate social support and presence of depressive symptoms in older adults to improve cardiac outcomes.